Combination BRAF/MEK Inhibitor Targeted Therapy and Immunotherapy (atezolizumab + vemurafenib + cobimetinib) for Metastatic Cutaneous Melanoma: Clinical Case - V. E. Askarov; A. V. Sultanbaev; K. V. Menshikov; V. S. Chalov; N. I. Sultanbaeva; I. A. Menshikova (Креативная хирургия и онкология)
Introduction. Cutaneous melanoma is a highly aggressive malignancy with a significant risk of metastasis. Current treatment strategies include surgical resection, immunotherapy, and targeted therapy directed at mutations in the MAPK/ ERK pathway, particularly BRAF V600E. Despite the efficacy of dual BRAF/MEK inhibition, the rapid development of drug resistance remains a challenge, prompting interest in combination immunotherapy plus targeted therapy. Aim. This study aimed to evaluate the efficacy and tolerability of triple therapy, involving atezolizumab, vemurafenib, and cobimetinib in patients with BRAF V600 mutation-driven metastatic melanoma following failure of prior lines of therapy. Materials and methods. We present a detailed case report of a patient with metastatic cutaneous melanoma who achieved disease stabilization for 27 months following surgery and first-line therapy with dabrafenib and trametinib. After subsequent progression, second- and third-line therapies with pembrolizumab followed by pembrolizumab and lenvatinib were administered; however, both therapies proved ineffective. Fourth-line therapy with atezolizumab, vemurafenib, and cobimetinib demonstrated a significant clinical response. Results and discussion. Following six months of triple therapy, positron emission tomography/computed tomography (PET/CT) confirmed complete metabolic regression of the previously identified lesions, including those in the intrathoracic lymph nodes and pulmonary metastases. The treatment was well tolerated, with no grade 3–4 adverse events. Conclusion. This clinical case highlights the potential of the atezolizumab, vemurafenib, and cobimetinib therapy in patients with pretreated BRAF V600E-mutated metastatic melanoma. This regimen may benefit patients with acquired resistance to BRAF/MEK inhibitors and immune checkpoint inhibitors. The findings underscore the importance of personalized treatment strategies and the need for further research in this area.